Effect of bath temperature on sodium diethyldithiocarbamate trihydrate loading of halloysite nanotube. Issue 1 (May 2020) - Kumar, S S; Kakooei, S; Ismail, M C; Haris, M
Abstract: Smart coatings have become one of the most sought after solutions for corrosion control in industries. A need to encapsulate the corrosion inhibitor by means of a nano/micro container has come into the picture as the conventional methods are not favourable and has demerits. Halloysite nanotube based smart coatings are effective given that it is environment-friendly unlike most of its competitors. The current work focuses on the effect of bath temperature in a vaporizer on the loading ability of Halloysite nanotube is studied with Sodium diethyldithiocarbamate trihydrate as a corrosion inhibitor. The loading was carried out at three different bath temperatures which are 40, 60 and 80 °C and the resultant samples were investigated by characterization using Scanning Electron Microscope (SEM), Fourier Transform Infrared Spectroscopy (FTIR) and UV-Vis Spectroscopy. It was found that an increase in bath temperature to 80 °C, it will increase the loading capacity of halloysite nanotubes.